2019
DOI: 10.1186/s12964-019-0385-8
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin type B receptor-mediated inhibition of A-type K+ channels enhances sensory neuronal excitability through the phosphatidylinositol 3-kinase and c-Src-dependent JNK pathway

Abstract: Background Cholecystokinin (CCK) is implicated in the regulation of nociceptive sensitivity of primary afferent neurons. Nevertheless, the underlying cellular and molecular mechanisms remain unknown. Methods Using patch clamp recording, western blot analysis, immunofluorescent labelling, enzyme-linked immunosorbent assays, adenovirus-mediated shRNA knockdown and animal behaviour tests, we studied the effects of CCK-8 on the sensory neuronal excitability and peripheral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…6 C, we observed a reduction in firing frequency in CCK-BR scFv-treated neurons compared to untreated neurons in the presence of CCK-8 (p < 0.0001, Mann-Whitney test). This concentration of CCK-8 used has previously been shown to sensitize sensory neurons in culture using electrophysiology assays ( Yu et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 C, we observed a reduction in firing frequency in CCK-BR scFv-treated neurons compared to untreated neurons in the presence of CCK-8 (p < 0.0001, Mann-Whitney test). This concentration of CCK-8 used has previously been shown to sensitize sensory neurons in culture using electrophysiology assays ( Yu et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work demonstrates that application of cholecystokinin, an endogenous agonist of CCK-B receptors, increases firing frequency of spinal dorsal root ganglia neurons through a decrease in A-type K + channel current (I A ) and caused mechanical and thermal hypersensitivity ( Yu et al, 2019 ). Indeed, our RNAseq studies indicate changes in several K + channel-related genes that would explain the effects of the scFv on nociceptor excitability, but requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism of CCK2R-mediated modulation of A-type K + currents involves the PI3K/SRC/JNK pathway. This signaling cascade results in the phosphorylation and, thus, the inhibition of A-type K + channels [48]. In the same study, the authors showed that intraplantar administration of CCK8 affected nociception in mice, characterized by mechanical and heat hypersensitivity, and that this effect was mediated by CCK2R and modulation of A-type currents.…”
Section: Cck/cck2r Decreases K + Channel Currentsmentioning
confidence: 90%
“…Inhibition of the transient type-A K + current by CCK-8/CCK2R activation has been recently shown in small-sized DRG neuron extracts from mice [48]. DRG neurons express a variety of A-type K + channels that regulate membrane excitability.…”
Section: Cck/cck2r Decreases K + Channel Currentsmentioning
confidence: 99%
“…Evidence for the involvement of CCK2R in pain sensitization/perception is abundant. For example, CCK2R has been confirmed as being expressed in dorsal root ganglion neurons to mediate the inhibition of a Kv current (I A ) to increase pain sensation [16]. The CCK2R antagonist is known to reduce the need for opioid administration in relieving pain in a mouse model of burn-induced pain [17], likely by antagonizing CCK2R-µ-opioid receptor (MOR) heterodimerization, which inhibits MOR signaling [18].…”
Section: Introductionmentioning
confidence: 99%